UNVEILING CONSUMER MOTIVATION: EXPLORING EXTRINSIC FACTORS AND THE WASIYYAH SERVICES IN MALAYSIA THROUGH SELF-DETERMINATION THEORY - Mursidi, Amalina (I-iECONS e-proceedings, 2023)
In Malaysia, the utilization of wasiyyah as a solution for the frozen assets problem has been acknowledged. However, despite its significance, the adoption rate of wasiyyah services remains low. This study aims to explore the factors influencing consumers’ extrinsic motivation and satisfaction in engaging with wasiyyah services, drawing upon the self-determination theory (SDT) and basic psychological needs theory (BPNT) as theoretical frameworks. Additionally, the study examines the mediating role of consumers’ extrinsic motivation in relation to satisfaction and basic psychological needs. An online survey yielded 182 responses, which were analyzed using partial least squares structural equation modelling (PLS-SEM). The results revealed that autonomy, competence, and relatedness significantly influence consumers’ extrinsic motivation. Furthermore, extrinsic motivation was found to impact satisfaction, and the findings indicated that extrinsic motivation mediates the relationship between autonomy, competence, relatedness, and satisfaction. The study underscores the substantial influence of consumers’ psychological needs, encompassing institutional factors, life events, and wealth management, on their extrinsic motivation. Furthermore, the significant role of extrinsic motivation in satisfaction provides valuable insights for industry players seeking to enhance their marketing strategies to attract more Malaysian Muslims to engage with wasiyyah services.